O Rio Grande do Norte no Brasil: uma contextualização em onze imagens - Raimundo Nonato Junior; Hervé Théry (Confins)
Rio Grande do Norte is a complex territory whose peculiarities can be observed more easily when compared to the general panorama of the Brazilian geographic space. In this perspective, the present work explores eleven geographical representations of the Brazilian space, comparing the national data to the regional issues of the state. The data treated refer to: population; demographic density; sectors of GDP; metropolises and urban hierarchies; theoretical area of influence of the metropolises; flows, airports and GDP; development index; cultural equipment; potential viewers; engines of development and efficiency of municipalities. The methodological approach uses assumptions and techniques that conceive the geographic space from its representational systems. The results point, in short, to Rio Grande do Norte as a "Geographic Complex" capable of articulating different actors, objects, scales and territorial actions.